Improving feeding efficiency of a sewing machine by on-line control of the presser foot - Silva, Luís F. (2004)
This paper presents a contribution towards the development of a new generation of sewing equipment integrating auxiliary add-on kits to improve performance and flexibility in the production of high-quality garments. An overview of all the recent developments concerning the redesign of the first PC-based controller developed for a novel electromagnetically actuated presser foot on an industrial overlock sewing machine will be presented. Other software modules, developed to ease the establishment of control references and the tuning of the controller parameters, as well as a brief discussion and analysis of the obtained results, will also be described in this paper. According to the latest results here reported, the presser foot firmly controls the fabric plies for a wide range of materials and situations.